2002
DOI: 10.7863/jum.2002.21.7.719
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Ethnicity and Variation of Fetal Femur Length Calculations When Screening for Down Syndrome

Abstract: There is a significant difference in the mean expected femur length by biparietal diameter among fetuses in the second trimester with regard to ethnicity. Using ethnic-specific formulas for expected femur length can have a considerable impact on the use of sonographic risk factors for Down syndrome screening. Further data are required for use of femur length as a screening tool in the genetic sonogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 11 publications
1
24
3
1
Order By: Relevance
“…However, similar results have been found for fetuses of African ancestry in Dutch and US cohorts [22,[24][25][26]. One UK study also showed that fetuses of African ancestry had a faster growth of crown-rump length during the first-trimester, compared with Europeans [27].…”
Section: Discussionsupporting
confidence: 68%
“…However, similar results have been found for fetuses of African ancestry in Dutch and US cohorts [22,[24][25][26]. One UK study also showed that fetuses of African ancestry had a faster growth of crown-rump length during the first-trimester, compared with Europeans [27].…”
Section: Discussionsupporting
confidence: 68%
“…Shorter femur was shown by just 1 out of the 31 of Down cases. Furthermore, previous studies report a high frequency of this marker among euploid individuals [21, 22]. In the present study, the risk increased 14-fold, with a very wide confidence interval, reflecting in low accuracy.…”
Section: Discussioncontrasting
confidence: 64%
“…Shortening of the fetal long bones such as the humerus and femur is a sonographic soft marker for screening of Down syndrome in the second trimester. Ethnic differences in fetal biometric measurements have been documented 1 3 . Beigi and ZarrinKoub 3 reported that Iranian fetuses had a shorter femur length in comparison with western studies.…”
mentioning
confidence: 99%
“…Beigi and ZarrinKoub 3 reported that Iranian fetuses had a shorter femur length in comparison with western studies. Kovac et al 1 concluded that Asian groups had a less‐than‐expected femur length.…”
mentioning
confidence: 99%